Edukasi Peduli Lingkungan melalui Pemanfaatan Botol Bekas sebagai Media Tanam di SDN 3 Keradenan - Robisha Zarifa Ribaah; Ahmad Sofi Yullah; Alex Haris Fauzi (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2026)
This community service program was implemented at SDN 3 Keradenan to raise students’ awareness of the importance of plastic waste management by reusing used plastic bottles as planters for ornamental plants. The issues identified were students’ limited understanding of the 3R concept (Reduce, Reuse, Recycle) and a lack of concern for the cleanliness of the school environment. The method used in this activity was a participatory approach that included initial observation, a student condition survey, program planning, socialization implementation, practical sessions on making plant pots from used bottles, monitoring and evaluation, and program follow-up. Socialization activities were conducted through material delivery, interactive discussions, and hands-on practice planting ornamental plants using recycled pots. The activity results showed an increase in students’ knowledge, awareness, and skills in managing plastic waste to create useful items. Students demonstrated high enthusiasm throughout the activity and began adopting environmentally conscious behaviors, such as properly disposing of waste, maintaining classroom cleanliness, and caring for the plants they had planted. This program also successfully enhanced students’ creativity in utilizing plastic waste as a beneficial planting medium. Additionally, the school environment became cleaner, greener, and more comfortable with the placement of ornamental plants throughout the school. Thus, this practice-based waste management education program is effective in fostering an environmentally conscious character among elementary school students.